Comparative Evaluation of Antimicrobial Efficacy of Silver Diamine Fluoride and Curodont™ Protect Remineralizing Agents on Streptococcus mutans: An In Vitro Microbiological Study - Vandana Chandran; M Smitha; Umme Azher; Santhosh T Paul (Journal of South Asian Association of Pediatric Dentistry)
Background: Dental caries is regarded as a biofilm-induced oral disease, with Streptococcus mutans assaying a pivotal part in the onset and progression of the carious lesion. Hence, controlling the bacterial load of the oral cavity is one of the elementary objectives in the prevention of dental caries. Objectives: To evaluate and compare the antimicrobial efficacy of silver diamine fluoride (SDF) and Curodont™ Protect remineralizing agents on S. mutans. Materials and methods: An in vitro microbiological study was conducted to ascertain the antibacterial efficacy of SDF (group I) and Curodont™ Protect remineralizing agent (group II) against S. mutans. Chlorhexidine gluconate (CHX) gel 2.0% w/w (group III) and distilled water (group IV) formed the positive and negative controls, respectively. The antibacterial efficacy was determined by agar well diffusion method following 24 hours of incubation, and the diameter of zones of inhibition (ZOI) was quantified. The data were statistically analyzed using Statistical Package for Social Sciences (SPSS) version 22.0. One-way analysis of variance (ANOVA) test was used to compare the mean ZOI between groups, and Tukey's post hoc test was used to compare the mean difference in the ZOI among groups (level of significance set at p < 0.05). Results: The mean ZOI was significantly higher for the SDF group (38.33 ± 0.58 mm) as compared to the CHX group (26.67 ± 0.58 mm), with a mean difference of 11.66 [95% confidence interval (CI)] at p < 0.001. Curodont™ Protect and distilled water did not demonstrate any ZOI. Conclusion: SDF tooth remineralizing agent exhibited higher antibacterial efficacy against S. mutans in comparison with Curodont™ Protect remineralizing agent.